علاقة السيطرة و الامومة السامة بين الأمهات المنحرفات النرجسيات و بناتهن -دراسة عيادية اسقاطية لحالتين عبر المقابلة العيادية و اختبار الرورشاخ و اختبار تفهم الموضوع - TAT - محجوبي إسراء; جودي حكيمة; اشراف: لبنى سفاري (جامعة محمد بوضياف -المسيلة, 2025)
تم الاعتماد في دراستنا المعنونة علاقة السيطرة و الامومة السامة بين الأمهات المنحرفات النرجسيات و بناتهن على المنهج العيادي و على مجموعة بحث تكونت من حالتي لبنتين أمهاتهما منحرفتين نرجسيتين ، تتراوح اعمار البنتين بين 20-25 سنة تنم انتقائهما بطريقة قصدية باعتماد جملة من المعايير اهمها مقياس الام المنحرفة النرجسية عبر مجموعة من الأدوات و المتمثلة في- المقابلة العيادية البحثية نصف الموجهة ، اختبار الرورشاخ، إختبار تفهم الموضوع (T.A.T) توصلنا الى النتائج التالية: - ترتبط علاقة السيطرة بالامومة السامة في علاقة الأمهات المنحرفات النرجسيات ببناتهن. - تظهر مؤشرات الامومة السامة بين الأمهات المنحرفات النرجسيات و بناتهن. - تظهر مؤشرات علاقة السيطرة بين الأمهات المنحرفات النرجسيات و بناتهن الكلمات المفتاحية: الام المنحرفة النرجسية، الامومة السامة، علاقة السيطرة Abstract Our study, titled "The Relationship Between Control and Toxic Motherhood Among Narcissistic Pervert Mothers and Their Daughters", was based on the clinical method and conducted on a research sample consisting of two cases of daughters aged between 20 and 25 years old, whose mothers are narcissistic pervert mothers. The participants were selected intentionally based on several criteria, the most important of which was the Narcissistic Pervert Mother Scale, along with a set of tools including: the semi-structured clinical research interview, the Rorschach Test, and the Thematic Apperception Test (T.A.T). The results showed the following: there is a relationship between control and toxic motherhood in the relationship between narcissistic pervert mothers and their daughters, indicators of toxic motherhood appear in the relationships between narcissistic pervert mothers and their daughters, indicators of control are evident in the relationships between narcissistic pervert mothers and their daughters Keywords: Narcissistic pervert mother, toxic motherhood, controlling relationship